Ecology of Finishing Processes - Ojstršek, Alenka; Fakin, Darinka; Gorgieva, Selestina (University of Maribor Press, 2024)
The script entitled “Ecology of Finishing Processes” is intended for students of the professional study programme Textile Deign Technologies. It is prepared in such a way that, in the first chapters, students are introduced to the basics of the technological processes of textile finishing and their ecological issues. Technological wastewaters present a specific problem in the textile industry as they are heavily loaded, contain various chemicals and textile auxiliaries, various types of organic dyes, have extreme pH values and high values of Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD), contain phosphates, sulphates and other salts, surfactants, fats and oils and various types of heavy metals. In addition, the alternative media and finishing processes are described, which use less chemicals and textile auxiliaries and less energy to achieve the selected finishing effect and, thus, have a lower impact on the environment. Special emphasis is placed on alternative processing techniques, which include automation, affecting further on lower water and energy consumption, a lower amount of waste, wastewater and greenhouse gas emission, as well as on higher productivity, safety at work and optimal use of working time. The gained knowledge will enable students with basic knowledge as well as advances approaches and technologies in the development and finishing of modern engineering materials.